Unleashing Public Private Partnership Understanding and the Ideal Underpinning Theories: A Public Sector View - Mugarura, Jude Thaddeo; Ndevu, Zwelinzima; Turyakira, Peter (Public Administration Research, 2020)
Researchers ceaselessly theorize public private partnerships (PPP) as a major innovative means to unlock public sector investment gaps, yet their contribution towards improved public service delivery has sustainably remained low mainly due to poor PPP understanding and application. This study utilises extant conceptual and theoretical studies through content analysis to provide a more concrete understanding of the PPP concept and philosophy for their effective application. The study developed a list of common PPP defining features (e.g. partnership, long-term projects and contracts, incomplete contracts, function specific tasks) and eight PPP perspectives (i.e. procurement management, urban regeneration, infrastructure, policy, moral regeneration, financing arrangements, language game, development) for better understanding of the PPP concept. Importantly, the study introduces a new and overarching PPP perspective of procurement management. Additionally, it was established that Traditional Public Management theory is not compatible with PPP practices, and the study recommends new public governance, public value, new public service, and remotely, the new public management as the most appropriate theories underpinning PPPs with in a public sector setting. This research contributes towards improved understandability of the PPP phenomenon and its practical applicability for greater impact towards sustainable public service delivery.
Keywords: Public private partnership; Theories; Definitions; Perspectives; Understanding